Charting the growth of idiopathic short stature research: a 32-year bibliometric study of global advances - Wang, Zhao; Gao, Zhendong; Huang, Yongdie; Li, Zhen; Luo, Fei; Li, Tao; Zhang, Yu; Lin, Lili; Wang, Shouchuan; Ye, Jin (Frontiers in Endocrinology, 2025)
IntroductionIdiopathic short stature (ISS) is a common paediatric endocrinological disorder defined by a height > two standard deviations (SDs) below the mean for age, sex, and ethnicity without an identifiable cause. This condition accounts for 60–80% of short stature cases in children and presents with complex and heterogeneous aetiology. ISS-related research has expanded rapidly over the past three decades; however, a comprehensive bibliometric analysis outlining its developmental trajectory and identifying emerging research priorities remains unavailable. Therefore, using network visualisation tools, we mapped 32 years of research to identify key trends, influential contributors, relevant journals, and emerging directions in ISS.MethodsPublications related to ISS in children, published between January 1993 and December 2024, were retrieved from the Web of Science Core Collection. Bibliometric and visual analyses were conducted using CiteSpace 6.1.R6, VOSviewer 1.6.20 and R package Bibliometrix. The analysis examined multiple dimensions, including annual publication trends, country and institutional contributions, collaboration networks, influential authors and journals, keyword evolution, and co-cited references to map the global ISS research landscape. We retrieved clinical trials published between 1993 and 2024 from the PubMed database to analyze the clinical progress in this field.ResultsA total of 1, 567 articles were included in the analysis. The volume of publications in the ISS field has steadily increased over time. The United States of America contributed the most publications. Leiden University in the Netherlands produced the highest number of institutional publications. Wit authored the greatest number of publications, whereas Ranke had the highest number of citations. The Journal of Clinical Endocrinology & Metabolism ranked first in both publication count and citation frequency. Co-citation analysis identified foundational documents, including the 2008 expert consensus led by Cohen, and the 2016 clinical guidelines spearheaded by Grimberg. Recent keyword bursts such as “heterozygous mutation, “ “guideline, “ and “variant” suggest growing attention to genetic mechanisms and precision medicine.DiscussionThis study systematically mapped the developmental trajectory and thematic evolution of ISS research over the past three decades using a comprehensive bibliometric analysis. The findings identified key contributors and research hotspots, providing valuable insights and reference points to guide future investigations.